Keragaman Tumbuhan Pakan Burung Cenderawasih di Hutan Kampung Rhepang Muaif Kabupaten Jayapura - Edoward Krisson Raunsay; Konstantina MB Kameubun; Alfred A. Antoh; Leonardo E. Aisoi; Papua Kapitarauw (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
The aim of this research is to carry out a vegetation analysis looking at the types of plants at the seedling, sapling, pole and tree level which have the potential to serve as food for birds of paradise. The plotted line method is a measuring tool used to collect vegetation data at the seedling, sapling, pole and tree level. The data obtained is then analyzed to determine Density, Relative Density, Dominance, Relative Dominance, Frequency, Relative Frequency, Importance Value Index and Diversity Index. The research results showed that 5 types of food sources were obtained, namely Palaquium amboinense, Gnetum gnemon, Pometia acuminata and Syzygium sp. The structure and composition of vegetation at the seedling level consists of 21 species with H' (2.74) or medium, the sapling level consists of 34 species with H' (3.16), the pole level 27 species with H' (2.83), tree level 38 species with H' (3.06). Keywords: Bird of Paradise, Food, Muaif Rhepang, Vegetation